Elementary Students' Gender Beliefs and Attitudes Following a 12-Week Arts Curriculum Focused on Gender. Issue 1 (2nd January 2020) - Vilkin, Ellora; Einhorn, Leslie; Satyanarayana, Satyanand; Eisu, Ammo; Kimport, Katrina; Flentje, Annesa
Abstract: Middle- and high school-based programs that affirm diverse sexual orientations and gender identities are related to lower rates of bullying and better mental health for LGBTQ students, yet little is known about how to implement affirming programs for elementary-aged children. This study is among the first to examine how an arts-based curriculum for grades K–5 that embraced expansive understandings of gender was related to children's gender attitudes and beliefs. Structured interviews queried beliefs and attitudes towards activities associated with traditional gender norms with 83 students in a California afterschool program. Following the curriculum, more students reported their gender in expansive terms, specific changes in gender norm beliefs were observed, and attitudes became more positive towards those who engage in gender-expansive roles, activities, and attire (e.g. a boy who becomes a mother). Results suggest that gender-focused arts-based curricula may be associated with increased awareness of gender norms, shifts in understandings of gender, and more positive attitudes toward gender-expansive roles, activities, and attire.